Disturbances on telephone lines and their remedies - Brown, Frank E.; Wilson, Edgar M. (My University, 1906)
Introduction: Telephone lines were first built with only one wire, the earth being used as a return circuit. It was soon found that the telephone receiver was so sensitive to electrical disturbances of all kinds that lines so constructed were rarely free from noises, and were often so seriously affected thereby as to render conversation almost impracticable. As other electrical industries multiplied the troubles increased, especially after the coming of the street railway that insisted upon using the earth as a return circuit for very large current. The disturbances became so great that the telephonists were confronted with a serious problem in an endeavor to render their circuits commercially quiet. A careful study of the origin of noises upon the telephone line revealed them to be due to several causes, leakage, electro-magnetic induction, and electro-static induction. The first that we will take up is leakage. It has been found from experience that few instruments have been invented which are as sensitive a detector for a varying current as the telephone receiver. It has been found that a current of less than a millionth of an ampere will readily effect a telephone receiver. If therefore a telephone line is so situated with respect to other electrical circuits that there can be an actual leakage of electricity to the telephone line, it is certain to produce so much disturbance as to render the use of the line impracticable. Then telephones are operated as grounded circuits, one end of the line is connected to the earth at one station and the other at some distant point. If there is a difference of potential between the earth at the two stations there is a tendency for foreign currents to flow over the line in an endeavor to equalize this difference of potential.
Citation: Brown, Frank E. and Wilson, Edgar M. Disturbances on telephone lines and their remedies. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Telephone Line; Telephone System; Theses